CHANGED CIRCUMSTANCES AND HARDSHIP IN THE INTERNATIONAL SALE OF GOODS - Niklas Lindström (Nordic Journal of Commercial Law, 2006)
The purpose of a contract is to establish the contracting parties’ rights and responsibilities under the contract. Both parties’ interest, at least at the time of entering into the contract, is to see that the contract is performed as agreed. It is essential that the parties to a contract are familiar with the contents of the contract and possible nonmandatory regulations that might complement the contract. A failure to perform a contract often results in liability for damages. Whether a party is liable for a breach of contract is largely dependent on how strict the liability is under the contract, i.e. which prerequisites must be fulfilled in order for liability to arise. In the United Nations Convention on Contracts for the International Sale of Goods (hereinafter the “ CISG” or the “ Convention” ) a party is liable for all events in its control. In other words a party is liable unless the event causing the breach of contract is beyond its control. After the conclusion of a contract but before the contract is performed a party’s situation may change due to changed circumstances, especially when the contract is to be performed over a long period of time or in a more distant future. In accordance with what could be called the foundation of contract law, pacta sunt servanda, changed circumstances are of no relevance with regard to a party’s rights and responsibilities under the contract. A breach of contract results in liability. It cannot, however, be regarded as reasonable that a party would always be required to perform the contract regardless of what happens with the surrounding circumstances. Such a legal state would be too harsh. Hence, it is important that a contract in exceptional cases can be adapted to changed circumstances. However, also situations where all contracts would automatically be entered into with a precondition that circumstances do not change or where contracts due to even slight changes would be adapted or avoided would be fatal for international trade. This would admittedly result in a flexible legal state but at the same time the contract as a legal transaction would lose its importance. The doctrine of pacta sunt servanda needs, thus, exceptions that can be applied in special circumstances. Most national legal orders contain such provisions. Some provisions allow a deviation from what has been agreed on only in cases of impossibility, other provisions allow a deviation also when the performance of a contract has become much more onerous but not impossible. Such provisions provide some flexibility to legal relations that can be regarded as appropriate and should not be in conflict with the general concept of justice. This Article discusses a breaching party’s exemption from liability under the CISG due to changed circumstances. The Article contemplates the relationship between the doctrine of hardship and an exemption from liability under the CISG. Under the CISG a party is responsible for all events in its control and a party’s liability is independent of its negligence. However, a party shall not be liable for a failure to perform the contract if the failure was due to an impediment beyond its control. It is important to discuss what can be regarded as an “impediment beyond control” , as the Article concentrates on a party’s possibility for an exemption in situations where a performance has become more expensive than expected and the equilibrium of the contract has been altered due to changed circumstances and a performance in the new situation would be something totally different than at the time of the conclusion of the contract. The latter can be referred to as a situation of hardship.